Evaluation of compression tests of thermopolymerizable acrylic resin when poly (diallyldimethylammonium chloride) is included in its mass (Research, Society and Development, 2021)
Introduction: Thermopolymerizable acrylic resins are widely used in dentistry because they have several satisfactory properties. These materials tend to undergo changes in their structure during use, which can cause inflammation and infections. The most diverse researches sought to develop a way to reduce this possibility and Dos Santos in 2020 evidenced that this material added with the biocide poly (diallyl dimethylammonium chloride) has an antibacterial and antifungal potential, indicating this increase only for prostheses that do not suffer any type of force during its use. Objective: to show the behavior of the thermopolymerized acrylic resin plus poly (diallyl dimethylammonium chloride) against compression tests seeking to evaluate its behavior in this situation. Methods: The compression tests were carried out using the double-column Instron3369 universal testing machine in front of two groups; G1 being the material without the addition of the biocide and G2 the material with the addition of the biocide. Results: The results showed that G2 undergoes more deformation requiring less compression force than G1. Conclusion: It is evident that there are losses in the mechanical properties of the thermopolymerized acrylic resin plus poly (diallyl dimethylammonium chloride), but that further tests are necessary for the future use or not of this material in different locations.